2008
DOI: 10.1111/j.1526-4610.2008.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Imaging Abnormalities Consistent With CSD During Migraine Without Aura Attack

Abstract: An 18-year-old man with a history of migraine without aura and normal neurological examination carried out a cerebral CT scan during a spontaneous typical migraine attack. While the CT scan demonstrated left temporal-parietal-occipital low attenuation, a brain magnetic resonance imaging, performed 5 days later, did not show any lesions. Based on this evidence, we can speculate that the dysfunction of the cerebrovascular system, either in the cerebral cortex or in the subcortical regions, is an important mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Some similar reported cases 23‐25 have shown that it is possible to observe these transitory images, suggesting a cytotoxic edema during the aura in brain computed tomography or MRI, and no lesion appears in FLAIR‐ or T2‐weighted images when a control brain MRI is performed several days after.…”
Section: Resultsmentioning
confidence: 70%
“…Some similar reported cases 23‐25 have shown that it is possible to observe these transitory images, suggesting a cytotoxic edema during the aura in brain computed tomography or MRI, and no lesion appears in FLAIR‐ or T2‐weighted images when a control brain MRI is performed several days after.…”
Section: Resultsmentioning
confidence: 70%
“…Cortical spreading depression (CSD) is thought to be a key mechanism in the pathophysiology of both MA (e.g. [28]) and MO [29]. Therefore, the high prevalence of MA in JME might be related to CSD starting more often in patients with JME than without JME.…”
Section: Discussionmentioning
confidence: 99%
“…migraine-prophylactic drugs [16]. Recently, it was reported that some patients with MWOA also showed reversible imaging abnormalities that were consistent with CSD, which began in the occipital lobes and subsequently spread anteriorly to the parietal and temporal lobes [27,28]. Moreover, it is now believed that MWOA and migraine with aura (MWA) share the same pathogenic mechanisms, which include CSD [29].…”
Section: Discussionmentioning
confidence: 97%